PENELITIAN AKUNTABILITAS ZAKAT DI INDONESIA: TINJAUAN LITERATUR TAHUN 2017-2021 - Khaerunisah, Khaerunisah; Baehaqi, Ahmad (Jurnal Riset Keuangan dan Akuntansi, 2023)
This study aims to examine the development of zakat accountability research literature in Indonesia in 2017–2021. This study uses secondary data in the form of journal articles in the economic field, which are categorized as Sinta 2, 3, and 4, so that 39 research articles related to zakat accountability in Indonesia are obtained. The research method used is a literature review with a content analysis approach. The results of the research show that the publication of zakat accountability research articles will increase in 2020. Yogyakarta Muhammadiyah University is an affiliated institution with the most publications. The use of quantitative and qualitative research methods is almost the same, which is dominated by descriptive analysis, SEM-PLS, and regression. Financial accountability is the most researched topic related to the dimensions of zakat accountability. This research contributes to the mapping of zakat accountability research in Indonesia so that it becomes input for further research. Keywords: Accountability, Zakat, Zakat Institutions, Literature Review